Media and Communication in Europe - Stepinska, Agnieszka (Logos Verlag Berlin, 2014)
This timely book explores how the media shape the Europeanization of the public sphere within the European Union (EU). Bringing together a range of international scholars in media studies and journalism and covering both traditional and online media, it argues that Europeanization is not just an idea - it is a real, ongoing process that we are experiencing every day. Assessing a wide range of actors and processes and acknowledging the diverse relationships between media and politics, the chapters edited by Agnieszka Stepinska reflect contemporary conceptualizations of Europeanization and unravel the complex mediatization of European politics. It covers topics as diverse as children's socialization within the European Union via kid's TV programmes; the impact of the 'Euroblogosphere' on policy decisions; and international broadcasting as one of the key elements to understanding new public diplomacy in Europe. Using the Polish EU presidency of 2011 as an extensive case study, the book's latter part shows what impact Poland's presidency had on its representation, both domestically and abroad, and questions the Presidency's actual power of attracting media attention. 'Media and Communication in Europe' is a valuable resource for any student and researcher interested in the complex relationship between the media and the EU.
Description based on print version record.
KU Select 2020: HSS Backlist Books
Keywords: Technology & Engineering / Agriculture; Social Science; Social sciences; Electronic books